Merging Motor and Cognitive Development: There's So Much to Learn While Being Physically Active! - Cheung, W. Catherine; Ostrosky, Michaelene M.; Hsiu-Wen Yang; Akamoglu, Yusuf; Favazza, Paddy C.; Aronson-Ensign, Katherine (Palaestra, 2019)
Children develop many school readiness skills such as motor and cognitive skills during the preschool years. The development of these skills requires repeated opportunities to practice. Many preschool teachers may not be aware that motor development provides a foundation for cognitive development, and they may be unsure how they can support motor and cognitive development simultaneously for children in inclusive classes. The purpose of this article is to highlight motor and cognitive skills that develop during the preschool years, followed by ideas on how to merge Fundamental Motor Skills (FMS) and Basic Relational Concepts during large and small groups activities. Readers will learn new ways to implement lessons in their classroom that facilitate motor and cognitive development so that children can gain basic conceptual knowledge while also gaining important motor skills.